Augered Cast-In-Place (ACIP) And Drilled Displacement (DD) Pile Quality Control ? Introduction - Rudolph P. Frizzi (Deep Foundations Institute, 2004)
Quality control is essential for augered cast-in-place (ACIP) piles (also known as continuous flight auger (CFA) piles outside the United States) and drilled displacement (DD) piles since the pile is constructed below the ground surface out of the direct sight of the personnel constructing and inspecting the pile. ACIP piles are being successfully constructed to support high-rise structures, hospitals, arenas and stadiums, mass transit systems, and power and industrial facilities. The use of DD pile technology is also gaining ground in the United States, typically utilizing proprietary systems such as Omega (currently utilized by Richard Goettle Inc., and LG Barcus and Sons, Inc.), Berkel, and DeWal (currently utilized by Morris-Shea). Different types of ACIP/DD pile installation equipment are shown in Figures 1 and 2. ACIP piles are installed into granular and cohesive soils, and soft rock to lengths currently approaching 130 ft (39.5 m), with diameters up to 24 to 36 inches (610 to 915 mm), and sustaining design loads approaching 900 kips (4000 kN). Current DD pile installation equipment in the United States is capable of installing up to 79-ft-long (24 m) piles with diameters ranging from 12 to 18 inches (305 mm to 460 mm).